2016
DOI: 10.18782/2320-7051.2218
|View full text |Cite
|
Sign up to set email alerts
|

Screening for sources of tolerance to drought in sesame induced mutants: Assessment of indirect selection criteria for seed yield

Abstract: INTRODUCTIONSesame (Sesamum indicum L., Pedaliaceae) is also called orphan crop. Nowadays, however world demand for its seeds is interestingly increasing owing to its good quality oil (50 %), protein (25 %) and for content of antioxidants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
5
20
1
Order By: Relevance
“…These statements can be verified from Table 4 and are in agreement with Van Rheenen (1981) who found no relationship between number of capsules and seed yield under rainfed conditions in Nigeria and in a world survey. These results are opposed to other studies (Boureima et al, 2016;Zhou et al, 2018) who reported a positive association between NCP and seed yield. This is why Cagirgan et al (2009) applied selection for number of capsules in the pairwise F2 populations of determinate and indeterminate crosses of sesame and estimated genetic gains comparatively by F3 generation means.…”
Section: Genotype By Trait Biplot (Gt) and Traits Relationshipcontrasting
confidence: 99%
“…These statements can be verified from Table 4 and are in agreement with Van Rheenen (1981) who found no relationship between number of capsules and seed yield under rainfed conditions in Nigeria and in a world survey. These results are opposed to other studies (Boureima et al, 2016;Zhou et al, 2018) who reported a positive association between NCP and seed yield. This is why Cagirgan et al (2009) applied selection for number of capsules in the pairwise F2 populations of determinate and indeterminate crosses of sesame and estimated genetic gains comparatively by F3 generation means.…”
Section: Genotype By Trait Biplot (Gt) and Traits Relationshipcontrasting
confidence: 99%
“…In sesame, the lack of efficient selection criteria hampered the development of improved cultivars for drought resistance [6]. Crop resistance to drought is achieved through diverse mechanisms which often work together indicating that different drought related traits must be investigated for an efficient screening of a germplasm [50].…”
Section: Important Traits For Efficient Screening For Drought Resistamentioning
confidence: 99%
“…Hence, sesame holds tremendous potential to sustainably improve livelihoods of poor farmers. However, because the crop is mostly grown under rain fed conditions in arid and semi-arid areas of West and Central Africa, it is often subjected to terminal and intermittent droughts [6]. Despite its relative tolerance to drought stress, severe or prolonged drought is detrimental for the productivity by affecting the number of capsules per plant, grain yield and oil yield and quality as well [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture, Sohag University, Sohag, Egypt. the essential amino acids such as linoleic acid, which is a source of vitamin E, calcium and phosphorous minerals (Weiss, 2000 andHamza &Abd El-Salam, 2015). In addition to them, it is being reported that this plant could be grown at the reclaimed soils (Boureima et al, 2016). Despite of all these advantages, the local production of sesame is 45 thousand tonnes, harvested from a small cultivated area of 32 thousand ha (FAOSTAT, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with a strong breeding program effective for developed high yielding genotypes under the abiotic stress in the reclaimed soil. Herein, Boureima et al (2016) reported that genetic and breeding improvement efforts in the sesame have been limited, making the results of such efforts slow to emerge. Effective selection criteria and additional genetic information for breeders are insufficient.…”
Section: Introductionmentioning
confidence: 99%